Disparities in the protagonism of oral health teams in the work process of Primary Healthcare - Érika Talita Silva; Raquel Conceição Ferreira; Fabiano Costa Diniz; Milena Ribeiro Gomes; Andréa Maria Eleutério de Barros Lima Martins; Loliza Luiz Figueiredo Houri Chalub; Maria Inês Barreiros Senna (Universidade de São Paulo, 2024)
ABSTRACT OBJECTIVE Evaluate and compare the protagonism of Oral Health teams (OHt) in the teamwork process in Primary Healthcare (PHC) over five years and estimate the magnitude of disparities between Brazilian macro-regions. METHODS Ecological study that used secondary data extracted from the Sistema de Informação em Saúde para a Atenção Básica (SISAB - Health Information System for Primary Healthcare) from 2018 to 2022. Indicators were selected from a previously validated evaluative matrix, calculated from records in the Collective Activity Form on the degree of OHt's protagonism in team meetings and its degree of organization concerning the meeting agendas. A descriptive and amplitude analysis of the indicators' variation over time was carried out, and the disparity index was also calculated to estimate and compare the magnitude of differences between macro-regions in 2022. RESULTS In Brazil, between 3.06% and 4.04% of team meetings were led by OHt professionals. The Northeast and South regions had the highest (3.71% to 4.88%) and lowest proportions (1.21% to 2.48%), respectively. From 2018 to 2022, there was a reduction in the indicator of the "degree of protagonism of the OHt" in Brazil and macro-regions. The most frequent topics in meetings under OHt's responsibility were the work process (54.71% to 70.64%) and diagnosis and monitoring of the territory (33.49% to 54.48%). The most significant disparities between regions were observed for the indicator "degree of organization of the OHt concerning case discussion and singular therapeutic projects". CONCLUSIONS The protagonism of the OHt in the teamwork process in PHC is incipient and presents regional disparities, which challenges managers and OHt to break isolation and lack of integration, aiming to offer comprehensive and quality healthcare to the user of the Unified Health System (SUS).